2013
DOI: 10.1016/j.yexcr.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative changes in the proteome of extracellular vesicles accompanying cancer cell transition to mesenchymal state

Abstract: Transitions of the cancer cell phenotype between epithelial and mesenchymal states is likely to alter the patterns of intercellular communication. In this regard we have previously documented that EMT-like changes trigger quantitative changes in exosomal vesicle emission in A431 cancer cells driven by oncogenic epidermal growth factor receptor (EGFR). Here we report that extracellular vesicles (EVs) produced by these cancer cells in their epithelial and mesenchymal states exhibit profound qualitative differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 66 publications
4
68
0
Order By: Relevance
“…cell-free DNA), individual EV carry multiple molecular entities, the combination of which could be informative as to complex properties and responses of EV donor cells. Despite considerable EV profiling efforts currently underway (19,(47)(48)(49), the analysis of molecular combinatorial co-emission patterns is scarcely available, especially given the remarkable heterogeneity both between and within the specific and still poorly characterized EV subpopulations (exosomes, ectosomes, and apoptotic bodies) (48). The EV-mediated co-emission of EGFR and exo-gDNA by cancer cells targeted with EKI, as described in our study, is but one example of such biologically meaningful combinatorial characterization.…”
Section: Discussionmentioning
confidence: 99%
“…cell-free DNA), individual EV carry multiple molecular entities, the combination of which could be informative as to complex properties and responses of EV donor cells. Despite considerable EV profiling efforts currently underway (19,(47)(48)(49), the analysis of molecular combinatorial co-emission patterns is scarcely available, especially given the remarkable heterogeneity both between and within the specific and still poorly characterized EV subpopulations (exosomes, ectosomes, and apoptotic bodies) (48). The EV-mediated co-emission of EGFR and exo-gDNA by cancer cells targeted with EKI, as described in our study, is but one example of such biologically meaningful combinatorial characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings suggest that hierarchical regulation of a subset of extracellular effectors may coordinate a biological response during EMT that enhances cell motility [128]. The same group also investigated the contribution of EVs during EMT in the same cell model and observed profound protein differences (i.e., a reprogramming) in the EV proteome upon EMT (see Section 4) [130,131]. The functional consequences of the proteome component of EVs being reprogrammed (especially the unique enrichment of oncogenic factors, master transcriptional regulators (e.g., YBX1) and core splicing subunits in mesenchymal cells) is intriguing and warrants further investigation [130].…”
Section: Contribution Of Extracellular Modulators During Emtmentioning
confidence: 93%
“…For example, Garnier et al reported that EMT induction in A431 mesenchymal-like cancer cells by epidermal growth factor receptor (EGFR) activation/blockade of E-cadherin, led to elevated secretion of EVs containing EGFR and tissue factor, thereby transferring the pro-coagulant activity to endothelial cells, an accelerated event during cancer malignancy [133]. Proteomic analysis revealed that EMT in cancer cells resulted in a qualitative redistribution of EV cargo proteins, where enriched proteins were involved in cellular growth, cell-to-cell signalling, and cell movement [131]. Others have used quantitative proteomics to characterize exosomes released from non-metastatic and metastatic models [134,135].…”
Section: Functional Contribution Of Evs During the Emt Processmentioning
confidence: 99%
“…Reports suggesting that given proteins are unique or enriched in specific EV populations from disease states are contributing to our understanding of disease markers generally[73, 80]. Recently, Muturi et al have demonstrated that EV signatures can be donor cell specific[81], and Garnier et al have identified EV signatures that discriminate cellular differentiation and transformation[82]. However, more extensive investigation on whether tumor cells can modulate their cargo in different phases of biological activity is missing.…”
Section: Exosomes and Microvesiclesmentioning
confidence: 99%